Demographic and clinical predictors of vitamin D status in pregnant women tested for deficiency in Western Australia. (2nd September 2021) - Miller, Kate M.; Klerk, Nick H. de; Davis, Elizabeth A.; Lucas, Robyn M.; Hart, Prue H.; Haynes, Aveni
Abstract: Objective : This study aimed to describe the vitamin D status of pregnant women in Western Australia and identify predictors of deficiency in pregnancy. Methods : A cross‐sectional study was conducted using linked data from statewide administrative data collections. Participants included pregnant women aged 18–44 years who gave birth between 2012 and 2014. Results : The mean 25‐hydroxyvitamin D (25[OH]D) concentration was 70.7 nmol L −1 (SD 25.7; range 5–255 nmol L −1 ). Approximately one‐fifth of the pregnant women were vitamin D deficient (<50 nmol L −1 ). Maternal age (under 25 years) was identified as an independent risk factor of vitamin D deficiency in addition to known predictors. Only 20% of women were screened within the first 10 weeks of their pregnancy. Conclusions : In addition to the existing risk factors for deficiency, maternal age was an independent predictor of vitamin D deficiency. There was a large discrepancy between the time of first antenatal visit and screening for vitamin D deficiency. Implications for public health : Our findings support the addition of maternal age (under 25 years) to the current clinical guidelines for targeted screening of 25(OH)D levels in pregnancy and the practical application of screening for vitamin D deficiency at the first antenatal visit.